2022
DOI: 10.1088/1742-6596/2374/1/012052
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation studies at the Bern cyclotron for the ATLAS ITk upgrade

Lea Halser

Abstract: At the high-luminosity LHC, the radiation levels for participating experiments will increase by over one order of magnitude in total ionising dose compared to current levels. Therefore, components and materials installed closest to the interaction points, such as the new ATLAS Inner Tracker (ITk), have to be tested for their durability in high-radiation environments. The variety and multitude of materials and components require a large number of irradiation campaigns. For this purpose, the irradiation facility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Another test is the operation of an Optoboard during irradiation. Results of irradiation tests on previous versions of the Optosystem have been presented in [17,18].…”
Section: Radiation Hardness Tests and System Testsmentioning
confidence: 99%
“…Another test is the operation of an Optoboard during irradiation. Results of irradiation tests on previous versions of the Optosystem have been presented in [17,18].…”
Section: Radiation Hardness Tests and System Testsmentioning
confidence: 99%
“…The Bern Medical Cyclotron was employed in order to verify the radiation resistance of the Optosystem. Previous irradiation studies are reported in [10]. This infrastructure, located at the Bern University Hospital, is primarily used for 18 F production, but it hosts an independently accessible research irradiation bunker which can be used for radiation hardness studies [9].…”
Section: Jinst 18 C03021 4 Test Of the Radiation Hardness Of The Opto...mentioning
confidence: 99%
“…To this end, diverse components such as cable shieldings, connectors and electrical cables have been irradiated. Figure 13 (left) shows the setup used to irradiate the cables connecting the detector front-end modules to the opto-electronic converters [35]. To achieve a uniform dose along the cable length, the cable was wrapped on a spool mounted on a motor, so that the spool could rotate during the irradiation.…”
Section: Examples Of Irradiation Campaignsmentioning
confidence: 99%